Valuation of target companies for acquisition: a general study on the techniques used by several companies in Malaysia / Zulkifli Mohd Salleh Sabai - Mohd Salleh Sabai, Zulkifli (1991)
In any acquisition, the offer price for the shares of the target company poses the most difficult question to answer: What is the appropriate purchase price for the target company? Both buyer and seller employ several valuation techniques to arrive at an acceptable price range. While all these techniques lead to an estimate of the value and price of the target, this project paper hopes to shed a little light on the techniques generally applied by acquisition-minded companies in Malaysia.